2018
DOI: 10.3892/ol.2018.7883
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitization of two human colon cancer cell lines to the antitumor effects of irinotecan combined with 5-aza-2'-deoxycytidine

Abstract: Abstract. Irinotecan (CPT-11) is a key therapeutic drug used in the treatment of colorectal cancer, although acquired or constitutive resistance to CPT-11 (and its activated metabolite SN-38) can lead to tumor progression. Since the acquisition of drug resistance can result from DNA hypermethylation, the antitumor activity of CPT-11 and SN-38 was assessed in combination with a known DNA methyltransferase inhibitor, 5-aza-2'-deoxycytidine, also known as decitabine (DAC). DAC potentiated the antitumor activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The anti-apoptotic gene, BCL2, which plays a role in programmed cell death as an antiapoptotic protein [ 47 ], was over-expressed when HCT-116 cells were treated with Terr alone under normoxic conditions; however, it was significantly downregulated when the cells were treated with the combination treatment (GCB + Terr). This observation is supported by similar combination studies that showed the downregulation of BCL2 when HCT-116 was treated with combination treatment [ 48 ].…”
Section: Discussionsupporting
confidence: 61%
“…The anti-apoptotic gene, BCL2, which plays a role in programmed cell death as an antiapoptotic protein [ 47 ], was over-expressed when HCT-116 cells were treated with Terr alone under normoxic conditions; however, it was significantly downregulated when the cells were treated with the combination treatment (GCB + Terr). This observation is supported by similar combination studies that showed the downregulation of BCL2 when HCT-116 was treated with combination treatment [ 48 ].…”
Section: Discussionsupporting
confidence: 61%
“…Several studies have reported that a combination of DNMT inhibitors, such as 5-aza-2’ deoxycytidine (DAC), with irinotecan could overcome irinotecan resistance by different mechanisms in human colon cancer cell models. We found that enhanced apoptosis by irinotecan was achieved in combination with DAC, through the downregulation of the anti-apoptotic gene Bcl-2 [ 67 ] . Bcl-2/adenovirus E1B 19 kDa protein-interacting protein (BNIP3), a pro-apoptotic gene, was methylated in human colon cancer cell lines.…”
Section: Clinical Problems In Irinotecan-based Therapy and Overcoming...mentioning
confidence: 99%
“…Indeed, another hypomethylating cytidine analogue, 5-aza-2′-deoxycytidine (DAC), enhanced the anticancer efficacy of CPT-11, the prodrug of irinotecan, additively and its active metabolite, 7-ethyl-10-hydroxycamptothecin (SN-38), synergistically. The extent to which DAC potentiates CPT-11 or SN-38 might be dependent on the expression level of anti-apoptotic Bcl-2 protein in human colorectal cancer cells, as the higher intracellular protein levels of Bcl-2 were shown to be associated with the resistance of cancer cells to CPT-11 and SN-38 [ 67–70 ]. Treatment with DAC before irinotecan significantly improved tumor suppression in a xenograft model with OCUM2 M/SN38 irinotecan-resistant gastric cancer cells.…”
Section: Epigenetic Modifications and The Response Of Cancer Cells To...mentioning
confidence: 99%